O efeito do atraso gradual do modelo ecoico na aquisição de tato e de mando em crianças com diagnóstico de autismo - Sousa, Isabella Luiza Debone de (2015)
Previous studies that proposed to install mand and tact in children diagnosed with Autism Spectrum Disorder, added to the training procedure different verbal antecedents, in addition to the ones under investigation that are supposed to control. The present study sought to assess a procedure to install mand and tact in four autistic children with gradually delay echoic prompt. Two different topographies were trained for each participant. The children were separated into two groups. The group number 1 was trained in the mand-tact route and the group number 2 in the tact-mand route. The results showed that the use of gradually delay echoic prompt was effective in the participants of the mand-tact route for one topography and for the verbal operant tact only. The follow up result showed that the correct answers by this participant were maintained after one month, and for the three others participants, it is noticeable a higher number of echoic answers related with the baseline for the two trained topographies